The Impact of α-Adrenoceptors in the Regulation of the Hypotonicity-Induced Increase in Duodenal Mucosal Permeability In Vivo - John Sedin; David Dahlgren; Markus Sjöblom; Olof Nylander (MDPI AG, 2021)
The duodenal mucosa is regularly exposed to a low osmolality, and recent experiments suggest that hypotonicity increases mucosal permeability in an osmolality-dependent manner. The aim was to examine whether the sympathetic nervous system, via action on α-adrenoceptors, affects the hypotonicity-induced increase in duodenal mucosal permeability. The duodenum of anaesthetised rats was perfused in vivo with a 50 mM NaCl solution in the presence of adrenergic α-adrenoceptor drugs. Studied were the effects on mucosal permeability (blood-to-lumen clearance of 51Cr-EDTA), arterial blood pressure, luminal alkalinisation, transepithelial fluid flux, and motility. Hypotonicity induced a six-fold increase in mucosal permeability, a response that was reversible and repeatable. The α2-adrenoceptor agonist clonidine abolished the hypotonicity-induced increase in mucosal permeability, reduced arterial blood pressure, inhibited duodenal motility, and decreased luminal alkalinisation. The α2-adrenoceptor antagonists, yohimbine and idazoxan, prevented the inhibitory effect of clonidine on the hypotonicity-induced increase in mucosal permeability. The α1-agonist phenylephrine or the α1-antagonist prazosin elicited their predicted effect on blood pressure but did not affect the hypotonicity-induced increase in mucosal permeability. None of the α1- or α2-adrenoceptor drugs changed the hypotonicity-induced net fluid absorption. In conclusion, stimulation of the adrenergic α2-adrenoceptor prevents the hypotonicity-induced increase in mucosal permeability, suggesting that the sympathetic nervous system has the capability to regulate duodenal mucosal permeability.